The Impact of Basketball Statistics on Winning a Game : Comparison of Czech NBL, Euroleague and NBA - Srp, Štěpán; Holý, Vladimír; Krautwurm, Petr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This thesis uses logistic regression to analyse which basic basketball statistics are important in determining the outcome of a game. The thesis compares six seasons of the Czech National Basketball League (NBL), Euroleague, and the NBA, both in the regular season and playoff, using only basic box score statistics or their derivatives. The created models were based on three different sets of predictors: the first set contained only offensive/defensive efficiency rating, the next set consisted of the so-called Four Factors, and the last one fitted ordinary statistics obtainable directly from box scores. The results suggest that efficient shooting, turnovers, and rebounding are among the most important factors to winning games in all leagues, with each league differing in which factors are more important. In the NBA, there was a larger emphasis on efficient shooting, the 3-point shot was more important than in other leagues, with an apparent upward trend over time. The Czech NBL and Euroleague tend to be more strategically oriented, emphasizing turnovers and rebounds more than in the NBA. Additionally, the European leagues showed less difference between playoff and regular season, while in the NBA, the difference in play style between the two was larger. In the NBA playoff, the game becomes more similar to Euroleague and Czech basketball, with a greater emphasis on rebounding, steals, and turnovers.
Vedoucí práce: Vladimír Holý
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor bakal. práce]; bakalářské práce; bachelor's theses